Immobilization of HIV‐1 TAT peptide on gold nanoparticles: A feasible approach for siRNA delivery. Issue 3 (31st July 2019) - Ahwazi, Razieh P.; Kiani, Melika; Dinarvand, Meshkat; Assali, Akram; Tekie, Farnaz S. M.; Dinarvand, Rasoul; Atyabi, Fatemeh
Abstract: RNA interference is one of the prosperous approaches for cancer treatment. However, small interfering RNA (siRNA) delivery to cancer cells has been faced with various challenges restricting their clinical application over the decades. Since ROR1 is an onco‐embryonic gene overexpressed in many malignancies, suppression of ROR1 by siRNA can potentially fight cancer. Herein, a delivery system for ROR1 siRNA based on HIV‐1 TAT peptide‐capped gold nanoparticles (GNPs) was developed to treat breast cancer. Besides, we introduced a new feasible method for conjugating the peptide to the nanoparticles. Since the GNPs have high affinity to the sulfur, the findings demonstrated the peptide successfully conjugated to the nanoparticles via Au–S bonds. As positively charged nanoparticles showed high cellular uptake, we could use a low concentration of nanoparticles led to high efficient gene transfection with negligible cytotoxicity that was confirmed by flow cytometry, confocal microscopy, gel retardation, and 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. Following transfection, downregulation of ROR1 and its targeted gene, CCND1, induced apoptosis in cancer cells. In conclusion, the reported capped GNPs could be potentially utilized for delivering negatively charged therapeutic agents in particular genes. Abstract : HIV‐1 TAT cell penetrating peptide is conjugated to gold nanoparticles by replacing with cetyltriethyl ammonium bromide molecules. The positively charged nanoparticles are able to interact with ROR1 small interfering RNA electrostatically. HIV‐1 TAT peptides enhance cellular uptake of the prepared complexes.